Developing a model for effective stakeholder engagement management - Sinclair, Marie-Louise (Deakin University Australia, 2011)
The maturing of corporate social performance as a management discipline has prompted a renewed interest in stakeholder-related concepts of management and receptivity to approaches which embed stakeholder engagement in the ‘business of business’. The stakeholder engagement function has moved from ‘nice to have’ to core business. This paper describes a five-year action research study to identify trends in corporate stakeholder engagement management and develop a stakeholder engagement management framework reflecting industry best practice.